2022
DOI: 10.1177/09612033211066462
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in Greek patients with systemic lupus erythematosus

Abstract: Objectives Vitamin D deficiency has been observed in autoimmune rheumatic diseases, such as rheumatoid arthritis. The aim was to study vitamin D in patients with systemic lupus erythematosus (SLE) and its relationship with disease activity. Methods In a cohort of 45 patients with SLE, 41 females and 4 males, aged 47.07 ± 2.17 years (mean ± SEM), and range = 21–79 years, 25(OH)D3 levels were determined by electrochemiluminescence. C3 and C4 levels were also analyzed. SLE disease activity was estimated by SLEDAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…For a long time, vitamin D deficiency has been known to play a vital role in the pathogenesis of autoimmune diseases ( 27 ). Reports have shown that patients with SLE have significantly insufficient vitamin D levels ( 13 ), as do those with other immune diseases, such as multiple sclerosis ( 14 ), autoimmune thyroid disorders ( 15 ), and antiphospholipid syndrome ( 16 ). There is increasing evidence that IgA vasculitis patients also have lower serum levels of vitamin D than healthy children, but most of these previous studies had small sample sizes ( 19 - 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, vitamin D deficiency has been known to play a vital role in the pathogenesis of autoimmune diseases ( 27 ). Reports have shown that patients with SLE have significantly insufficient vitamin D levels ( 13 ), as do those with other immune diseases, such as multiple sclerosis ( 14 ), autoimmune thyroid disorders ( 15 ), and antiphospholipid syndrome ( 16 ). There is increasing evidence that IgA vasculitis patients also have lower serum levels of vitamin D than healthy children, but most of these previous studies had small sample sizes ( 19 - 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-known functions of regulating calcium and phosphorus metabolism, and maintaining bone health, vitamin D has a broad regulatory effect on the immune system ( 11 , 12 ). Studies have shown that vitamin D deficiency is prevalent in autoimmune diseases, such as systemic lupus erythematosus (SLE) ( 13 ), multiple sclerosis ( 14 ), autoimmune thyroid disorders ( 15 ), and antiphospholipid syndrome ( 16 ). A systematic review showed that SLE patients had significantly lower vitamin D levels than healthy controls ( 13 ), and lower vitamin D levels were associated with SLE disease pathogenesis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies against vitamin D may also be related to its low levels in SLE [ 144 , 150 ]. Low C 3 and C 4 levels may be related to low vitamin D levels in SLE, and both are related to increased disease activity [ 151 , 152 ]. Lupus nephritis may be related to low vitamin D [ 152 , 153 ].…”
Section: Systemic Lupus Erythematosus and Vitamin Dmentioning
confidence: 99%
“…Low C 3 and C 4 levels may be related to low vitamin D levels in SLE, and both are related to increased disease activity [ 151 , 152 ]. Lupus nephritis may be related to low vitamin D [ 152 , 153 ]. In lupus and nephritis patients, VDR expression was studied with immunohistochemistry in renal biopsy specimens.…”
Section: Systemic Lupus Erythematosus and Vitamin Dmentioning
confidence: 99%
“…The administration of vitamin D (1,200 IU/d vs. placebo) over 4 months (from December to March) significantly reduced the incidence of influenza A in school-aged children by 42% ( Urashima et al, 2010 ). Vitamin D deficiency has also been associated with various autoimmune diseases, including systemic lupus erythematosus ( Athanassiou et al, 2022 ). More recently, vitamin D deficiency was proposed as a possible factor in the susceptibility, severity, and mortality of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection ( Jain and Parsanathan, 2020 ; Razdan et al, 2020 ).…”
Section: Vitaminsmentioning
confidence: 99%